Microphotoluminescence investigation of InAs quantum dot active region in 1.3 μm vertical cavity surface emitting laser structure - Ding, Y. (2013)
Microphotoluminescence -PL investigation has been performed at room temperature on InAs quantum dot QD vertical cavity surface emitting laser VCSEL structure in order to characterize the QD epitaxial structure which was designed for 1.3 m wave band emission. Actual and precise QD emission spectra including distinct ground state GS and excited state ES transition peaks are obtained by an edge-excitation and edge-emission EEEE -PL configuration. Conventional photoluminescence methods for QD-VCSELs structure analysis are compared and discussed, which indicate the EEEE -PL is a useful tool to determine the optical features of the QD active region in an as-grown VCSEL structure. Some experimental results have been compared with simulation results obtained with the aid of the plane-wave admittance method. After adjustment of epitaxial growth according to EEEE -PL measurement results, QD-VCSEL structure wafer with QD GS transition wavelength of 1300 nm and lasing wavelength of 1301 nm was obtained.